A classification system to enhance light‐fastness data interpretation based on microfading tests and rate of colour change. (30th August 2017) - Prestel, Thomas
Abstract : In general light‐fastness tests are carried out by comparing the colour change of a sample to the colour change of Blue Wool Standards in the same illumination conditions. With the microfading technique, developed to test the light fastness of a tiny test area on objects of cultural value, this comparison is made by absolute colour change after exposure. This article presents a new approach to enhance data interpretation of light‐fastness tests by the use of the rate of colour change. The procedure is combined with the conventional classification process using absolute colour change. The new classification system with the rate of colour change was applied to 44 samples, 13 of them were classified in more sensitive Blue Wool categories when analysing the rate of colour change. The perspective of rate of colour change helps to enhance data interpretation especially of samples showing fading characteristics different from the light‐fastness standards.